1993
DOI: 10.1071/rd9930001
|View full text |Cite
|
Sign up to set email alerts
|

The unique stability of the marsupial sperm acrosomal membranes examined by unprotected freeze-thawing and treatment with the detergent Triton X-100

Abstract: In this study of the unique stability of the marsupial acrosome, experiments were carried out on the acrosomes of spermatozoa of the tammar wallaby (Macropus eugenii), common brushtail possum (Trichosurus vulpecula) and grey short-tailed opossum (Monodelphis domestica). Light microscopy showed that 4% of opossum and 15% of possum and wallaby spermatozoa lost their acrosomes after freeze-thawing. Electron microscopy revealed that freeze-thawing also induced changes in the acrosomal matrix of some acrosome intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although the marsupial acrosome is generally thought to be resistant to cryoinjury (Sistina et al 1993, Breed et al 2001, Johnston & Holt 2001, this might still be a plausible explanation for co-localisation of initial DNA damage and the peri-acrosomal region in this study. Although the marsupial acrosome is known to be highly stable, even to the repeated effects of a freeze-thaw procedure (Sistina et al 1993), rupture or more subtle damage of the underlying nuclear or acrosomal membranes might still occur in the peri-acrosomal region during cryopreservation. These events could plausibly induce digestion of proteins associated with these chromatin domains and may then lead to secondary structural changes in the adjacent DNA.…”
Section: Discussionmentioning
confidence: 84%
“…Although the marsupial acrosome is generally thought to be resistant to cryoinjury (Sistina et al 1993, Breed et al 2001, Johnston & Holt 2001, this might still be a plausible explanation for co-localisation of initial DNA damage and the peri-acrosomal region in this study. Although the marsupial acrosome is known to be highly stable, even to the repeated effects of a freeze-thaw procedure (Sistina et al 1993), rupture or more subtle damage of the underlying nuclear or acrosomal membranes might still occur in the peri-acrosomal region during cryopreservation. These events could plausibly induce digestion of proteins associated with these chromatin domains and may then lead to secondary structural changes in the adjacent DNA.…”
Section: Discussionmentioning
confidence: 84%
“…It has been hypothesised that the acrosome is so located to maximise contact between its surface and that of the outer matrix of the zona pellucida, to facilitate spermzona binding and penetration (Bedford, 1991(Bedford, , 1996(Bedford, , 1998. Furthermore, in contrast to the sperm chromatin, the acrosome appears to be more stabilised than that of eutherians (Cummins, 1980, Mate & Rodger, 1991Sistina et al 1993) and it has been suggested that such stabilisation may be due to disulphide bonding of proteins within the acrosomal membranes and\or matrix (Lin et al 1995).…”
Section: mentioning
confidence: 99%
“…Furthermore, and perhaps related to this mode of zona penetration, the spermatozoa of nearly all species of marsupials lack disulphide bonding of protamines in the chromatin (Balhorn, 1989 ;, thus rapid decondensation and dispersion of sperm chromatin occurs during air drying (Bedford & Calvin, 1974 ;Cummins, 1980). Conversely the acrosome of marsupial sperm is thought to be highly stabilised so that on air drying, it, unlike the nucleus, apparently does not undergo dispersion of its contents nor is it dispersed either after freezing or thawing or with ' moderate ' detergent treatment (Mate & Rodger, 1991 ;Sistina et al 1993). It has been suggested that the stability of the acrosomal membranes and\or matrix may be due to the presence of disulphide bonded proteins which, unlike in eutherians, are not present in the chromatin (Lin et al 1995).…”
Section: mentioning
confidence: 99%
“…Sperm of most marsupials have a dorso-ventrally flattened nuclear surface (Temple-Smith 1994) and there is a more stable acrosome on the dorsal nuclear surface (Mate & Rodger 1991, Sistina et al 1993. During epididymal transit, changes in acrosomal morphology occur, and the sperm head rotates on its axis from a T-shape relative to the tail to become aligned with it (Temple-Smith 1994, Lin & Rodger 1999.…”
Section: Introductionmentioning
confidence: 99%